Crack nucleation from non-metallic inclusions in aluminum alloys described by peridynamics simulations. (December 2021) - Rezaul Karim, Mohammad; Kadau, Kai; Narasimhachary, Santosh; Radaelli, Francesco; Amann, Christian; Dayal, Kaushik; Silling, Stewart; Germann, Timothy C.
Highlights: Establish peridynamics framework for the description of the crack nucleation process from a cluster of non-metallic inclusion. Crack nucleation process characterizes as multiple micro-crack nucleation events from individual inclusions. Identifies four stages of crack nucleation process such as nucleation initiation, micro-crack initiation, technical and crack initiation. Crack nucleation phase depends on inclusion density, flaw size, grain boundary strength as well as the interface strength between inclusion and matrix material. Abstract: Conventional engineering methods oftentimes have challenges in the quantification of crack nucleation processes from manufacturing defects that are relevant for engineering component lifing. We present peridynamic simulation framework for the description of the crack nucleation process from cluster of non-metallic inclusions in aluminum alloys. Our non-local simulation framework characterizes crack nucleation process as multiple micro-crack nucleation events from individual inclusions, and eventually one micro-crack dominates. We define individual stages of the crack nucleation process, i.e., nucleation, micro-crack, technical, and crack initiation, that allow a quantification and meta model development of both the individual stages and the entire crack nucleation process.